Phytochemical and proximate content of Sago Leaves their use as natural tea alternatives - Rehena, Zasendy; Nendissa, Andriana Ritje; Siahaya, Griennasty Claudya (Agrikan Jurnal Agribisnis Perikanan, 2023)
The aims of this study were to find out 1) The use of sago leaves as a substitute for natural tea for the people in Kamal Village, West Seram Regency, 2) The proximate content (carbohydrates, proteins and fats) of sago leaf tea. 3) Phytochemical Test (alkaloid compounds, Flavonoids, terpenoids, phenols and tannins) of sago leaf tea,. This type of research 1). Qualitative descriptive research using a survey approach to find out the use of sago leaves by the community, 2) Analytical descriptive research using a laboratory approach to test the proximate content of sago leaf tea consisting of analysis of protein, fat and carbohydrate content, also testing other chemical contents (phytochemical test). sago leaf tea namely alkaloids, flavonoids, tannins, and saponins. The results showed that out of 15 respondents there were 8 respondents who had used sago leaves as a substitute for tea leaves by boiling the shoots. The proximate test results showed that sago leaf tea contained a small amount of protein with an average protein content of 0.0698, sago leaf tea did not contain fat or carbohydrates. Phytochemical test results showed that sago leaf tea contained alkaloids (0.0529%), flavonoids (0.0224%), phenols (0.5616%), and tannins (0.5610%).